Design and Development of a Website-Based Cooperation Information System at the Faculty of Engineering, University of Riau - Putri Ramadhani Muliaqalbi; Dian Ramadhani (Journal of Software Engineering and Multimedia (JASMED), 2025)
The management of cooperation activities at the Faculty of Engineering, University of Riau was previously conducted manually and via disparate platforms, which created inefficiencies in document distribution and cooperation-duration monitoring. This study aims to design and develop a centralized cooperation information system to support administrative and monitoring processes within the faculty. The system was developed using the Prototype method and evaluated according to the ISO 25010 standard. The evaluation results indicate very high functional suitability, strong performance efficiency, high usability, and excellent scores in reliability, maintainability, security, portability, and compatibility. These findings suggest that the developed cooperation information system effectively improves the efficiency and accuracy of cooperation management and provides a comprehensive solution for centralized cooperation administration at the Faculty of Engineering